Coating with excellent medium-temperature salt spray corrosion resistance as well as preparation method and application of coating
The Cr2AlC MAX phase coating prepared by using the dual-target HIPIMS composite synchronous bias pulse method solves the problem of medium-temperature salt spray corrosion in the marine atmospheric environment and achieves excellent corrosion resistance of the coating in the medium-temperature marine atmospheric environment.
Patent Information
- Application Number
- CN202411564580.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-01-21
AI Technical Summary
Medium-temperature salt spray corrosion in marine atmospheric environments causes serious damage to the compressor blades of carrier-based aircraft engines, and the existing MAX phase coating still has room for improvement in corrosion resistance in this environment.
The CR2ALC MAX phase coating is used to prepare through the dual -target HIPIMS composite synchronous polarization pulse method. The coating has (110) selection of best, columnar crystal structure and high purity, to ensure that a uniform and dense oxidation layer is formed in the medium -temperature ocean atmospheric environment.
In a medium-temperature marine atmospheric environment, the coating structure is dense, the morphology is complete, the oxide layer is uniform, the corrosion area is small, and the protective effect is significantly better than that of Cr2AlC coatings prepared by other methods.
Smart Images

Figure CN119332209A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of material surface treatment, and in particular relates to a coating with excellent resistance to medium-temperature salt spray corrosion, a preparation method thereof, and an application thereof. Background Art
[0002] Marine corrosion is a threat to marine development. It can damage the structures of equipment and facilities, shortening their service life, and poses a significant threat to national economy and people's livelihoods. Severe corrosion can also cause sudden disasters, pollute the environment, and endanger the lives and property of the public.
[0003] Taking the shipborne aircraft engines in service in the marine atmosphere as an example, the air in the service environment is humid and the water vapor contains high salt content. - 、NO3 - Plasma, with its active chemical properties, can cause severe corrosion in blades. Furthermore, high-speed compressor blades collide with particles in the air, creating surface defects. Furthermore, the temperature of the compressor blades can reach 600°C due to the compression of the air. These complex and harsh service environments make blades extremely susceptible to failure, severely impacting their service life and increasing the probability of engine failure. Once cracks or even fractures develop in high-speed rotating blades, this can impact engine performance, causing surge, speed drop, and other failures. In severe cases, it can damage other engine parts, impacting flight safety and even leading to catastrophic flight accidents. Using protective coatings to protect metal components in marine atmospheric environments, ensuring they possess excellent corrosion resistance, is an effective approach to addressing marine corrosion.
[0004] The moderate-temperature salt spray corrosion in this marine environment causes significant damage to materials, and the demand for new materials in protective coatings is becoming increasingly urgent. MAX phase coatings, with their excellent corrosion resistance, have attracted widespread attention. MAX phases are a large class of thermodynamically stable, nano-layered metal carbides or nitride ceramic materials with a close-packed hexagonal structure. M primarily represents IVB-VIB transition metals, A primarily comes from Group III or IV elements, and X represents C or N. The atomic structure consists of alternating MX flakes and tightly packed layers of pure A atoms stacked in the C direction. X-position atoms generally fill the octahedral gaps formed by M-position atoms. Due to the weak bonding between MA atoms, MA bonds preferentially break at high temperatures, forming M and A oxides on the material surface, which in turn protect the substrate. Cr2AlC is a typical representative of MAX phase materials, which exhibits excellent resistance to chemical corrosion and high-temperature oxidation.
[0005] At present, the preparation process of MAX phase materials is mature. How to further improve its corrosion resistance and extend its service life in harsh service environments, especially to protect the matrix material from loss, has important research value and significance. Summary of the Invention
[0006] In order to solve the above-mentioned technical problems, the present invention provides a coating with excellent resistance to medium-temperature salt spray corrosion, a preparation method and application thereof. After the coating of the present invention is corroded in a medium-temperature marine atmospheric environment, the coating still has a dense structure, complete morphology, a uniform oxide layer, and a very small corrosion area. The protection effect is far superior to Cr2AlC coatings prepared by other methods.
[0007] The present invention provides a coating with excellent resistance to medium-temperature salt spray corrosion. The coating is a Cr2AlC MAX phase coating, the phase purity of the Cr2AlC MAX phase coating is greater than 85%, the coating has a (110) preferred orientation, the grains of the coating present a columnar crystal structure, and the thickness of the coating is 3-6 μm.
[0008] Compared with the prior art, the coating of the present invention has a higher (110) preferred orientation, large grains and a columnar crystal structure. Thanks to this structure, the oxide layer is generated quickly during corrosion, the oxide layer is uniform and dense without obvious defects, and no Cr appears in the oxide sublayer. x C y The porous structure further improves its resistance to oxidative corrosion. Subsequent actual working condition corrosion simulation experiments have verified that after corrosion in a medium-temperature marine atmosphere, the coating still has a dense structure, complete morphology, a uniform oxide layer, and a very small corrosion area. The protection effect is far superior to Cr2AlC coatings prepared by other methods.
[0009] In some embodiments, the coating is prepared using protective gas Ar as the working gas, a dual-target HIPIMS composite synchronous bias pulse method, and a CrAl alloy target and a C target as target materials.
[0010] A second object of the present invention is to provide a method for preparing a coating having excellent resistance to medium-temperature salt spray corrosion, the preparation method specifically comprising the following steps:
[0011] The deposition chamber was heated to 600-700°C. Under the magnetic pole configuration of the CrAl alloy target and the C target forming a closed magnetic field, argon gas was introduced under high vacuum conditions and the gas pressure was maintained stable. At the same time, the pulsed negative bias of the HIPIMS of the CrAl alloy target and the C target and the substrate was turned on, and the coating was deposited using the dual-target HIPIMS composite synchronous bias pulse method.
[0012] Compared with the existing technology, the present invention has the following advantages: the use of HiPIMS and synchronous pulse bias technology improves the kinetic conditions of coating growth, extends the diffusion distance of film-forming ions, thereby improving the density of the coating and the membrane-substrate bonding performance. The coating surface is smooth, the composition is uniform, there is no large particle accumulation, and the structure is dense.
[0013] In some embodiments, the parameters of the dual-target HIPIMS composite synchronous bias pulse method are as follows: the CrAl alloy target and the C target both use a HiPIMS power supply, and the power of the CrAl alloy target is 90-150 W, and the power of the C target is 120-180 W, wherein the parameters of the HiPIMS power supply are: frequency of 500-1000 Hz, period of 1000-2000 μs, duty cycle of CrAl alloy target of 2.5%, pulse time of 50-100 μs, duty cycle of C target of 5%, pulse time of 100-200 μs; the parameters of the pulsed negative bias power supply of the substrate are as follows: frequency of 500 Hz, amplitude of 100-200 V, duty cycle of 12.5-25%, pulse width of 250-500 μs, delay of 10-20 μs, and deposition time of 360-720 min.
[0014] In some embodiments, before depositing the coating, the substrate is further etched. The specific steps of the etching are as follows: heating the deposition chamber to 200-300°C, using a CrAl alloy target as a sputtering target, introducing argon gas under high vacuum conditions and maintaining a stable gas pressure, using HiPIMS technology, and applying a synchronous pulsed negative bias power supply to the substrate at the same time, and etching the substrate with Cr metal ions and Al metal ions for 30-60 minutes.
[0015] In some embodiments, the parameters of the etching process are as follows: the power of the CrAl alloy target is 90-150 W, the power of the C target is 120-180 W, wherein the parameters of the HiPIMS power supply are: frequency of 500 Hz, duty cycle of 2.5-10%, pulse width of 50 μs, and power of 100-180 W; the parameters of the pulsed negative bias power supply of the substrate are as follows: frequency of 500 Hz, amplitude of 900 V, and duty cycle of 2.5-10%.
[0016] In some embodiments, before the etching process, the substrate is also cleaned, and the cleaning process specifically includes the following steps: first, the substrate after wire cutting is polished from 200# to 3000# in ascending order using silicon carbide metallographic sandpaper, and then the substrate is polished to a mirror surface using diamond polishing agent, and then the polished substrate is ultrasonically cleaned using acetone and ethanol in sequence.
[0017] In some embodiments, the specific operation of introducing argon gas under high vacuum conditions and maintaining the gas pressure stable is: evacuating the chamber to 5×10 -4 After the pressure drops below Pa, 15-20 sccm of argon is introduced, and the pressure in the chamber is adjusted to stabilize at 0.6-1 Pa during the vacuum pumping process.
[0018] In some embodiments, the sizes of the CrAl alloy target and the C target are both 50.8×5 mm, the target material purity of the CrAl alloy target and the C target is both 99.9%, and the Cr:Al atomic ratio of the CrAl alloy target is 60:40.
[0019] The third object of the present invention is to provide a coating with excellent resistance to medium-temperature salt spray corrosion for use in aircraft engine compressor blades in a marine atmospheric environment.
[0020] In some embodiments, the present invention further provides a method for detecting corrosion failure of a blade protective coating in a simulated marine atmosphere environment to verify its corrosion resistance in a medium-temperature salt spray environment, comprising:
[0021] (1) First, dry and weigh the sample after coating deposition. Then, evenly spray the NaCl solution on the sample and dry and weigh it again. The sample will gain weight due to the NaCl deposition on the surface. Repeatedly spray evenly, dry and weigh it, and then calculate and control the salt weight gain per unit area. This will control the degree of solid NaCl deposition on the sample surface.
[0022] (2) Connect a steam generator to one end of the high-temperature tube furnace and set a certain temperature for the high-temperature tube furnace. After all the equipment is turned on and stabilized for a period of time, a large amount of uniform steam will continue to flow out from the other end of the high-temperature tube furnace. Place the substrate sample obtained in step (1) into the tube furnace that has reached the predetermined temperature and has evenly passed through the steam. After a period of time, remove the sample and observe the corrosion condition.
[0023] Among them, in step (1)
[0024] The cleaning steps of the metal substrate are as follows: first, the substrate after wire cutting is polished from 200# to 3000# in sequence using silicon carbide metallographic sandpaper, then polished to a mirror surface using diamond polishing agent, and then the polished substrate is ultrasonically cleaned using acetone and ethanol.
[0025] The precision of the balance is 0.0001 g.
[0026] The method for calculating the weight gain of salt per unit area is: (weight of the sample after multiple spraying and drying-weight of the sample dried before spraying) / area of the spraying area.
[0027] In step (2)
[0028] The temperature of the high temperature tube furnace is set to 450-650°C according to the working conditions.
[0029] The equipment startup steps are as follows: first, heat the high-temperature tube furnace to a predetermined temperature; second, start the steam generating device; set the steam temperature to 120°C; and keep the steam pipeline at 120°C. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 Schematic diagram of the synchronous pulse bias current waveform in Example 1;
[0031] Figure 2 Surface morphologies of the coating prepared in Example 1 and the coating prepared in Comparative Example 1, respectively;
[0032] Figure 3 XRD comparison diagrams of the coating prepared in Example 1 and the coating prepared in Comparative Example 1;
[0033] Figure 4 Surface corrosion conditions of the coating prepared in Example 1 and the coating prepared in Comparative Example 1 tested in a simulated marine atmosphere environment are compared;
[0034] Figure 5 The figures are respectively comparative diagrams of the cross-section corrosion conditions of the coating prepared by Example 1 and the coating prepared by Comparative Example 1 tested in a simulated marine atmospheric environment. DETAILED DESCRIPTION
[0035] To make the above-mentioned objects, features, and advantages of the present invention more clearly understood, specific embodiments of the present invention are described in detail below. It should be noted that the following embodiments are only intended to illustrate the implementation methods and typical parameters of the present invention, and are not intended to limit the parameter ranges described in the present invention. Reasonable variations derived therefrom are still within the scope of protection of the claims of the present invention.
[0036] It should be noted that the endpoints of the ranges and any values disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoints of each range, the endpoints of each range and individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be considered to be specifically disclosed herein.
[0037] Unless otherwise defined, all terms, symbols and other scientific terms used herein are intended to have the same meaning as commonly understood by those skilled in the art to which the present invention belongs. In some cases, terms with conventional meanings are defined herein for the purpose of clarification or ease of reference, and such definitions herein should not be construed as indicating significant differences from conventional understandings in the art. The technical methods described or cited herein are generally well understood by those skilled in the art and are adopted by conventional methods. Unless otherwise stated, the use of commercially available kits, reagents and instruments was carried out in accordance with the protocols and parameters given by the manufacturers.
[0038] The technical effects of the present invention are described below with reference to specific embodiments.
[0039] In the present invention, the material of the substrate may be Inconel718 or TC4 alloy.
[0040] Example 1
[0041] In this embodiment, the metal matrix material is Inconel 718 nickel-based alloy, which is a new method provided by the invention patent. The specific preparation method is as follows:
[0042] Use silicon carbide metallographic sandpaper to grind the Inconel 718 nickel-based alloy substrate from low to high grit to 3000#, and then use diamond polishing agent to polish it to a mirror surface;
[0043] The polished substrate was cleaned with acetone and ethanol for 15 minutes each, and then fixed to a specific metal plate with screws after air drying.
[0044] Set the deposition chamber temperature to 300°C and wait until the chamber vacuum is reduced to 5×10 -4 When the pressure is below 0.6 Pa, 20 sccm of high-purity argon gas is introduced into the vacuum deposition chamber to adjust the pressure in the chamber to 0.6 Pa.
[0045] The CrAl target and the C target were both powered by a HiPIMS power supply. The CrAl target power supply parameters were 500 Hz frequency, 2.5% duty cycle, 50 μs pulse width, and 120 W power. The C target was set to the DC mode in the HiPIMS equipment, with a power of 105 W and a negative bias supply voltage of 100 V.
[0046] The temperature of the deposition chamber was raised to 650°C, and Cr2AlC was deposited on the surface of the Inconel 718 nickel-based alloy substrate after etching and cleaning using HiPIMS technology. High-purity Ar gas with a pressure of 0.6 Pa was introduced into the vacuum chamber. Under the magnetic pole configuration in which the CrAl target and the C target formed a closed magnetic field, the HiPIMS of the CrAl target and the C target were turned on at the same time, with the powers set to 100 W and 120 W, respectively. The parameters of the HiPIMS power supply were set to: frequency, 500 Hz, period 2000 μs, duty cycle of CrAl target 2.5%, pulse time 50 μs, duty cycle of C target 5%, pulse time 100 μs. The Cr2AlC MAX phase coating was deposited using dual-target high-power pulsed magnetron co-sputtering composite synchronous pulse bias technology. The frequency of the substrate's pulse negative bias was 500 Hz, amplitude 100 V, duty cycle 5%, pulse width 100 μs, delay 10 μs (relative to the start of the metal target discharge pulse), and deposition time was 360 min.
[0047] The bias waveform during the deposition process in this embodiment is as follows: Figure 1 As shown; Figure 2 The surface morphology of the coating prepared in this embodiment and the coating prepared in comparative example 1 is shown. Figure 2 It can be seen that there is no large particle accumulation on the surface of the coating prepared in this embodiment, and the coating surface is smooth, the composition is uniform, and the structure is dense; Figure 3 The XRD comparison diagram of the coating prepared in this embodiment and the coating prepared in comparative example 1 is shown. Figure 3 It can be seen that the coating exhibits a (110) preferred orientation.
[0048] Example 2
[0049] In this embodiment, the metal substrate material is TC4 titanium alloy, and the specific preparation method of the MAX phase coating on the substrate surface is as follows:
[0050] Use silicon carbide metallographic sandpaper to grind the Inconel 718 nickel-based alloy substrate from low to high mesh to 3000#, and then use diamond polishing agent to polish it to a mirror surface;
[0051] The polished substrate was cleaned with acetone and ethanol for 15 minutes each, and then fixed to a specific metal plate with screws after air drying.
[0052] Set the deposition chamber temperature to 300°C and wait until the chamber vacuum is reduced to 5×10 -4 When the pressure is below 0.6 Pa, 20 sccm of high-purity argon gas is introduced into the vacuum deposition chamber to adjust the pressure in the chamber to 0.6 Pa.
[0053] Both the CrAl and C targets were powered by a HiPIMS power supply. The CrAl target power supply parameters were 500 Hz frequency, 2.5% duty cycle, 50 μs pulse width, and 120 W power. The C target was set to DC Mode in the HiPIMS instrument, with a power of 105 W and a negative bias supply voltage of 100 V.
[0054] The temperature of the deposition chamber was raised to 650°C, and Cr2AlC was deposited on the surface of the Inconel 718 nickel-based alloy substrate after etching and cleaning using HiPIMS technology. High-purity Ar gas with a pressure of 0.6 Pa was introduced into the vacuum chamber. Under the magnetic pole configuration in which the CrAl target and the C target formed a closed magnetic field, the HiPIMS of the CrAl target and the C target were turned on at the same time, with the powers set to 100 W and 120 W, respectively. The parameters of the HiPIMS power supply were set to: frequency, 500 Hz, period 2000 μs, duty cycle of CrAl target 2.5%, pulse time 50 μs, duty cycle of C target 5%, pulse time 100 μs. The Cr2AlC MAX phase coating was deposited using dual-target high-power pulsed magnetron co-sputtering composite synchronous pulse bias technology. The frequency of the substrate's pulse negative bias was 500 Hz, amplitude 100 V, duty cycle 5%, pulse width 100 μs, delay 10 μs (relative to the start of the metal target discharge pulse), and deposition time was 360 min.
[0055] Application Examples
[0056] This application example simulates the service conditions of the coating prepared in Example 1 under a marine atmosphere to evaluate the protective effect of the coating. The specific steps are as follows: the coating prepared in Example 1 is placed in a drying oven at 150°C for 10 minutes to completely remove the moisture on the surface of the sample. The sample is then taken out and the surface area of the coating is measured and calculated to be 4.1 cm 2 , with a mass of 1.1780g. Subsequently, a 25wt.% NaCl solution was sprayed onto the coating surface in the form of small droplets and placed in a drying oven for drying. The coating was weighed again to be 1.1785g. The second spraying of the salt solution and drying and weighing yielded a mass of 1.1791g. The third spraying of the salt solution and drying and weighing yielded a mass of 1.1796g… This process was repeated. The eighth spraying of the salt solution and drying and weighing yielded a mass of 1.1821g. Compared to the initial sample, the weight increased by 4.1mg, indicating that the NaCl salt deposition amount was 1mg / cm 2 First, turn on the high-temperature tube furnace and set its final temperature to 600°C with a heating time of 60 minutes. Once the tube furnace reaches the desired temperature, heat the sample to 120°C with steam. After stabilizing for 10 minutes, place the sample in the center of the tube furnace and set the holding time to 1200 minutes. After the holding time is complete, remove the sample and air cool it. Observe the corrosion of the coating. Figure 4Surface corrosion conditions of the coating prepared in Example 1 and the coating prepared in Comparative Example 1 tested in a simulated marine atmosphere environment are compared; Figure 5 The following are comparison diagrams of the cross-sectional corrosion conditions of the coating prepared in Example 1 and the coating prepared in Comparative Example 1 tested in a simulated marine atmosphere environment; Figure 4 and Figure 5 It can be seen that the coating prepared by the embodiment of the present invention has very beneficial corrosion resistance.
[0057] Comparative Example 1
[0058] This comparative example is Cr2AlC obtained without synchronous pulse biasing. This method is an existing conventional method. The specific preparation process is as follows:
[0059] In this comparative example, the metal substrate material is TC4 titanium alloy, and the specific preparation method of the coating with high MAX phase on the substrate surface is as follows:
[0060] Use silicon carbide metallographic sandpaper TC4 titanium alloy substrate to grind from low to high mesh to 3000#, and then use diamond polishing agent to polish it to a mirror surface.
[0061] The polished substrate was cleaned with acetone and ethanol for 15 minutes each, and then fixed on a specific metal plate with screws after air drying.
[0062] Set the deposition chamber temperature to 300°C and wait until the chamber vacuum is reduced to 5x10 -4 When the pressure drops below 2 Pa, introduce 50 sccm of high-purity argon gas into the vacuum deposition chamber and adjust the pressure to 2 Pa. Set the negative bias power supply to 450 V and observe the glow in the chamber, indicating that the Ar ions are etching and cleaning the substrate. The cleaning time is 30 minutes.
[0063] Both the CrAl and C targets were powered by a HiPIMS power supply. The CrAl target power supply parameters were 500 Hz, 2.5% duty cycle, 50 μs pulse width, and 120 W power. The C target was set to DC mode in the HiPIMS instrument, with a power of 105 W and a negative bias voltage of 100 V. Deposition time was 360 minutes.
[0064] Comparative Example 2
[0065] This comparative example is Cr2AlC obtained without synchronous pulse biasing. This method is an existing conventional method. The specific preparation process is as follows:
[0066] In this comparative example, the metal substrate material is TC4 titanium alloy, and the specific preparation method of the coating with high MAX phase on the substrate surface is as follows:
[0067] Use silicon carbide metallographic sandpaper TC4 titanium alloy substrate to grind from low to high mesh to 3000#, and then use diamond polishing agent to polish it to a mirror surface.
[0068] The polished substrate was cleaned with acetone and ethanol for 15 minutes each, and then fixed on a specific metal plate with screws after air drying.
[0069] Set the deposition chamber temperature to 300°C and wait until the chamber vacuum is reduced to 5×10 -4 When the pressure drops below 2 Pa, introduce 50 sccm of high-purity argon gas into the vacuum deposition chamber and adjust the pressure to 2 Pa. Set the negative bias power supply to 450 V and observe the glow in the chamber, indicating that the Ar ions are etching and cleaning the substrate. The cleaning time is 30 minutes.
[0070] Both the CrAl and C targets were powered by a HiPIMS power supply. The CrAl target power supply parameters were 500 Hz, 2.5% duty cycle, 50 μs pulse width, and 120 W power. The C target was set to DC mode in the HiPIMS instrument, with a power of 105 W and a negative bias voltage of 100 V. Deposition time was 360 minutes.
[0071] Application comparison
[0072] This comparative example simulates the service conditions of the prepared coating in a marine atmosphere to evaluate the protective effect of the coating. The coating prepared in comparative example 1 was placed in a drying oven at 150°C for 10 minutes to completely remove the moisture on the surface of the sample. The sample was then taken out and the surface area of the coating was measured and calculated to be 4.1 cm 2 , with a mass of 1.1642g. Subsequently, a 25wt.% NaCl solution was sprayed on the coating surface in the form of small droplets and placed in a drying oven for drying. The coating was weighed again to be 1.1647g. The second spraying of the salt solution and drying and weighing yielded a mass of 0.1651g. The third spraying of the salt solution and drying and weighing yielded a mass of 0.1657g… This process was repeated. After the eighth spraying of the salt solution and drying and weighing, the mass was 1.1683g. Compared with the initial sample, the weight increased by 4.1mg, that is, the amount of NaCl salt deposited on the coating surface was 1mg / cm 2 First, turn on the high-temperature tube furnace and set its final temperature to 600°C with a heating time of 60 minutes. Once the tube furnace reaches the desired temperature, heat the sample to 120°C with steam. After stabilizing for 10 minutes, place the sample in the center of the tube furnace and set the holding time to 1200 minutes. After the holding time is complete, remove the sample and air cool it. Observe the corrosion of the coating. Figure 4 Surface corrosion conditions of the coating prepared in Example 1 and the coating prepared in Comparative Example 1 tested in a simulated marine atmosphere environment are compared; Figure 5The following are comparison diagrams of the cross-sectional corrosion conditions of the coating prepared in Example 1 and the coating prepared in Comparative Example 1 tested in a simulated marine atmosphere environment; Figure 4 and Figure 5 It can be seen that the coating prepared by the embodiment of the present invention has very beneficial corrosion resistance.
[0073] Although the present disclosure is disclosed as above, the protection scope of the present disclosure is not limited thereto. Those skilled in the art can make various changes and modifications without departing from the spirit and scope of the present disclosure, and these changes and modifications will fall within the protection scope of the present invention.
Claims
1. A coating having excellent resistance to medium-temperature salt spray corrosion, characterized in that: The coating is a Cr2AlC MAX phase coating, and the phase purity of the Cr2AlC MAX phase coating is greater than 85%. The coating has a (110) preferred orientation, the grains of the coating present a columnar crystal structure, and the thickness of the coating is 3-6 μm.
2. The coating having excellent resistance to medium-temperature salt spray corrosion according to claim 1, characterized in that: The coating is prepared by using protective gas Ar as working gas, adopting a double-target HIPIMS composite synchronous bias pulse method, and using a CrAl alloy target and a C target as target materials.
3. A method for preparing a coating having excellent resistance to medium-temperature salt spray corrosion as claimed in claim 1 or 2, characterized in that: The preparation method specifically comprises the following steps: The deposition chamber is heated to 600-700°C. In a magnetic pole configuration in which the CrAl alloy target and the C target form a closed magnetic field, argon gas is introduced under high vacuum conditions and the gas pressure is maintained stable. At the same time, the HIPIMS of the CrAl alloy target and the C target and the pulsed negative bias of the substrate are turned on, and the coating is deposited using a dual-target HIPIMS composite synchronous bias pulse method.
4. The method for preparing a coating having excellent resistance to medium-temperature salt spray corrosion according to claim 3, characterized in that: The parameters of the dual-target HIPIMS composite synchronous bias pulse method are as follows: both the CrAl alloy target and the C target use a HiPIMS power supply, and the power of the CrAl alloy target is 90-150W, and the power of the C target is 120-180W, wherein the parameters of the HiPIMS power supply are: frequency of 500-1000Hz, period of 1000-2000μs, duty cycle of the CrAl alloy target of 2.5%, pulse time of 50-100μs, duty cycle of the C target of 5%, pulse time of 100-200μs; the parameters of the pulsed negative bias power supply of the substrate are as follows: frequency of 500Hz, amplitude of 100-200V, duty cycle of 12.5-25%, pulse width of 250-500μs, delay of 10-20μs, and deposition time of 360-720min.
5. The method for preparing a coating having excellent resistance to medium-temperature salt spray corrosion according to claim 3, characterized in that: Before depositing the coating, the substrate is also etched. The specific steps of the etching are as follows: the deposition chamber is heated to 200-300°C, a CrAl alloy target is used as a sputtering target, argon gas is introduced under high vacuum conditions and the gas pressure is maintained stable, HiPIMS technology is used, and a synchronous pulse negative bias power supply is applied to the substrate at the same time, and the substrate is etched with Cr metal ions and Al metal ions for 30-60 minutes.
6. The method for preparing a coating having excellent resistance to medium-temperature salt spray corrosion according to claim 5, characterized in that: The parameters of the etching treatment are as follows: the power of the CrAl alloy target is 90-150W, the power of the C target is 120-180W, the parameters of the HiPIMS power supply are: frequency is 500Hz, duty cycle is 2.5-10%, pulse width is 50μs, power is 100-180W; the parameters of the pulsed negative bias power supply of the substrate are as follows: frequency is 500Hz, amplitude is 900V, duty cycle is 2.5-10%.
7. The method for preparing a coating having excellent resistance to medium-temperature salt spray corrosion according to claim 5, characterized in that: Before the etching process, the substrate is also cleaned, and the cleaning process specifically includes the following steps: first, the substrate after wire cutting is polished from 200# to 3000# in sequence using silicon carbide metallographic sandpaper, and then the substrate is polished to a mirror surface using a diamond polishing agent, and then the polished substrate is ultrasonically cleaned using acetone and ethanol in sequence.
8. The method for preparing a coating having excellent resistance to medium-temperature salt spray corrosion according to claim 3 or 5, characterized in that: The specific operation of introducing argon gas under high vacuum conditions and maintaining stable gas pressure is as follows: evacuate the cavity to 5×10 -4 After the pressure drops below Pa, 15-20 sccm of argon is introduced, and the pressure in the chamber is adjusted to stabilize it at 0.6-1 Pa during the vacuum pumping process.
9. The method for preparing a coating having excellent resistance to medium-temperature salt spray corrosion according to claim 3 or 5, characterized in that: The sizes of the CrAl alloy target and the C target are both 50.8×5 mm, and the target material purity of the CrAl alloy target and the C target is both 99.9%. The Cr:Al atomic ratio of the CrAl alloy target is 60:
40.
10. Use of the coating having excellent resistance to medium-temperature salt spray corrosion as claimed in claim 1 or 2 in compressor blades of aircraft engines in a marine atmosphere environment.